Response to COVID-19 vaccination: Psychological stress and intentions of nursing personnel in Taiwan - Yu-Ping Wu; Chung-Ying Lin; Hao-Yun Kao; Yen-Chiao Angel Lu; Chi-Chang Chang; Chiu-Hsiang Lee; Musheer A. Aljaberi (Human Vaccines & Immunotherapeutics)
Although the COVID-19 pandemic has been officially declared over, the global community must remain prepared for future outbreaks. In this regard, understanding the factors associated with willingness to get vaccinated among healthcare workers – given their critical role in infection control – remains essential. Therefore, this study aims to investigate the factors associated with nursing personnel’s intention to get vaccinated against COVID-19. Using an online questionnaire survey from April to June 2022, 492 nurses (mean age = 34.4 years, SD = 13.4; 96.7% females) from different settings (including inpatient, outpatient, and ambulatory clinics) participated in the present study. With the use of SmartPLS 4.0, the Partial Least Squares Structural Equation Modeling (PLS-SEM) results showed that intention to get vaccinated was negatively associated with fear of COVID-19 (standardized coefficient = −0.149; p < .01) and vaccine hesitancy (standardized coefficient = −0.168; p < .01) but positively associated with informational support (standardized coefficient = 0.416; p < .01). Those with a higher intention to get vaccinated were positively associated with higher levels of no regrets regarding having received the vaccination (standardized coefficient = 0.544; p < .01). Moreover, fear, informational support, and vaccine hesitancy together explained 28.5% of the variance in intention to get vaccinated. In turn, the intention to get vaccinated explained 30.1% of the variance in the feeling of no regrets regarding having received the vaccination. Based on the results, addressing fear of COVID-19 through educational interventions, strengthening support systems, and promoting positive vaccination intentions may collectively improve vaccination rates among healthcare workers.